The relationship of climatic elements to the consumption of electricity and the extent to which it affects the efficiency of the solar system in Baghdad - Farej, Mithaal Taleb; Shanshool, Alaa Mohsen (Al-Adab Journal, 2021)
This research aims to estimate the quantitative relationship between the elements of the climate in Baghdad and the amount of electricity consumption in Baghdad for(2006-2017), and the climatic elements were statistically tested for the purpose of tracking what the change of any element of the climate can cause in the consumption of electric power, so the element of solar radiation, temperature, wind, rain, dust storms and analysis of the quantitative relations between them using the Pearson correlation coefficient and draw conclusions.